Glycine nitrogen in total parenteral nutrition: two prospective clinical trials comparing the efficacy of high and low glycine containing amino acid solutions. Issue 6 (June 1992) - Rees, R G; Payne James, J J; Grimble, G K; Halliday, D; Frost, P G; Silk, D B
Abstract : Glycine has been regarded as a poor source of nitrogen for total parenteral nutrition. Two prospective randomised cross over controlled clinical trials were undertaken to compare the efficacy of high and low glycine containing amino acid solutions in parenterally fed malnourished hypoalbuminaemic patients with gastrointestinal disease. In the first study (n = 9), amino acid solutions in which glycine accounted for 23% and 4% of total nitrogen were compared. No statistically significant difference was found in urea nitrogen/total urinary nitrogen excretion (mean (SEM) 83.4 (1.4) v 81.6 (1.7)%, p = 0.31), nitrogen balance (-1.9 (2.4) v -0.6 (2.0) g/day, p = 0.31) or plasma protein concentrations and blood urea nitrogen. In the second extended study (n = 5), there was no significant difference in net whole body protein synthesis (+1.3 (4.7) v-0.2 (3.7) mg/kg/hour, p = 0.69) or fractional (0.403 (0.070) v 0.480 (0.41)%/hour, p = 0.68) and absolute albumin synthesis rates (6.0 (0.9) v 7.2 (0.06) mg/kg/hour, p = 0.22), on comparing solutions of 25% and 8% glycine nitrogen. In addition, a significantly higher proportion of total urinary nitrogen comprised urea when patients received the low glycine containing amino acid source (81.4 (2.5) v 83.8 (3.2)%, p = 0.04). It is concluded that there are no apparent short term nutritional or metabolic disadvantages to using amino acid solutions that contain up to 25% of nitrogen as glycine in total parenteral nutrition.